Effects of photoperiod change on serum hormone level, hair follicle growth and antioxidant status in skin tissue of cashmere goats - Mao, Chenyu; Yin, Xuelei; Wang, Chu; Huang, Xinran; Li, Jiawen (Frontiers in Veterinary Science, 2025)
The growth of cashmere in goats was primarily influenced by natural photoperiod. However, whether artificially altering the photoperiod modified the rhythm of cashmere growth still required verification. In this study, the effects of photoperiod change on hormone secretion, hair follicle development, gene expression and skin antioxidant status of goats were studied in non-growth period of cashmere. Eighteen goats were randomly divided into three groups: control group (CG, natural photoperiod), short-day photoperiod group (SDPP, light 8 h/d, dark 16 h/d) and shortening photoperiod group (SPP, illumination duration gradually shortened from 16 h/d to 8 h/d). Experiment lasted for 60 days. Blood samples were taken weekly in first 30 days and every other day in last 30 days to determine hormone concentration. Skin samples were collected on 30 d and 60 d to determine hair follicle morphology, gene expression and skin antioxidant index. The results showed that SDPP and SPP increased the melatonin concentration on 34 d (p < 0.05) and 44 d (p < 0.05), and the epidermal growth factor concentration on 46 d (p < 0.05) and 50 d (p < 0.05), and the T3 concentration on 48 d and 56 d (p < 0.05), but decreased the prolactin concentration on 44 d (p < 0.05) and 56 d (p < 0.05), respectively. Additionally, on the 60 d, SDPP and SPP increased the depth of secondary hair follicle and the width of primary hair bulb (p < 0.05) and SPP increased the width of secondary hair bulb (p < 0.05). Furthermore, on the 60 d, SDPP up-regulated the β-catenin expression; SPP up-regulated the β-catenin, BMP2 and PDGFA expression (p < 0.05). Besides, on the 30 d, SDPP increased the activity of catalase (CAT) (p < 0.05) and decreased the content of malonaldehyde (MDA) (p < 0.05). On the 60 d, SPP increased the activities of total superoxide dismutase, both SDPP and SPP increased the activities of CAT and glutathione peroxidase (GPx) (p < 0.05), and decreased content of MDA in skin (p < 0.05). In addition, at 60 d, both SDPP and SPP up-regulated the gene expression of SOD1, GPx4 and CAT (p < 0.05). It can be seen that shortened the photoperiod affected the hair follicle activity by altering the secretion of hormone and mediating the expression of key genes, made hair follicle morphological changes. Meanwhile, short photoperiod improved the antioxidant capacity, created favorable conditions for cashmere growth.